Characteristics and Immunomodulating Functions of Adipose-Derived and Bone Marrow-Derived Mesenchymal Stem Cells Across Defined Human Leukocyte Antigen Barriers - Waldner, Matthias; Zhang, Wensheng; James, Isaac B.; Allbright, Kassandra; Havis, Emmanuelle; Bliley, Jacqueline M.; Almadori, Aurora; Schweizer, Riccardo; Plock, Jan A.; Washington, Kia M.; Gorantla, Vijay S.; Solari, Mario G.; et al. (Frontiers in Immunology, 2018)
Background: Vascularized Composite Allotransplantation (VCA) opens new possibilities in reconstructive transplantation such as hand or face transplants. Lifelong immunosuppression and its side-effects are the main drawbacks of this procedure. Mesenchymal stem cells (MSC) have clinically useful immunomodulatory effects and may be able to reduce the burden of chronic immunosuppression. Herein we assess and compare characteristics and immunomodulatory capacities of bone marrow- and adipose tissue derived MSC isolated from the same human individual across defined human leukocyte antigen (HLA) barriers. Material and Methods: Paired samples of omental (o.) adipose tissue, subcutaneous (s.c.) adipose tissue and bone marrow aspirate from 10 human organ donors were retrieved and MSCs isolated. Cells were characterized by flow cytometry and differentiated in three lineages: adipogenic, osteogenic and chondrogenic. In mixed lymphocyte reactions (MLR), the ability of ASCs and BMSCs to suppress the immune response was assessed and compared within individual donors. HLA mismatched, or mitogen stimulations were analyzed in co-culture with different MSC concentrations. Supernatants were analyzed for cytokine contents. Results: All cell types, s.c. ASC, o. ASC and BMSC demonstrated individual differentiation potential and cell surface markers. Immunomodulating effects were dependent on dose and cell passage. Proliferation of responder cells was most effectively suppressed by s.c. ASCs and combination with BMSC resulted in highly efficient immunomodulation. Immunomodulation was not cell contact-dependent and cells demonstrated a specific cytokine secretion. Conclusion: When human ASCs and BMSCs are isolated from the same individual, both show effective immunomodulation across defined HLA barriers in vitro. We demonstrate a synergistic effect when cells from the same biologic system were combined. This cell contact independent function underlines the potential of clinical systemic application of MSCs.